THE ANALYSIS OF SETTLEMENT QUALITY USING GIS IN MEDAN LABUHAN - Ayu Podesta; Nina Novira (Tunas Geografi, 2020)
This study aims to determine: (1) the quality of the residential neighborhood in the District of Medan Labuhan, (2) the distribution of the quality of the residential neighborhood in the District of Medan Labuhan. This research was conducted in Medan Labuhan District in 2020. All settlements in the Medan Labuhan sub-district are the research subjects. Data collection techniques used in this research are Image interpretation of Quickbird satellite imagery, field checks, and documentation. The data analysis technique used is descriptive qualitative analysis, quantitative analysis, and overlay analysis. The results of this study indicate that: (1) the quality level of the residential neighborhood in Medan Labuhan District is classified as medium with an area of 822.13 hectares or 84.24% of the residential area of Medan Labuhan District. (2) the distribution of the quality of the residential neighborhood is divided into three classifications, the widest one in the good quality level is in Pekan Labuhan with a total of 1 residential block covering an area of 21.1 Ha or 2.16% of the area of the residential block in Medan Labuhan District. Whereas for medium classification and poor classification, the widest range is in Kelurahan Besar with 22 settlement blocks covering an area of 216.36 hectares and poor classification with a total of 6 settlement blocks covering an area of 38.32 Ha or 22.17%  and 3.92% of the area of the residential block in Medan Labuhan District respectively.